The effect of grass cover on bank erosion. - Tengbeh, G. Tamba (Cranfield University, 1989)
The scour experiments on the bare root-free and root-permeated soils indicated that for each soil, critical tractive force (CTF) linearly increases with both root density and vane shear strength. However, for both soilsq CTF was mainly related to vaneýshear strengthp indicating the potential importance of soil shear strength as an index of scour erodibility of cohesive channel bank materials. The analysis of the relative effects of the grass vegetation parameters on scour resistance confirmed the dominance of vegetation shoots relative to the roots in resisting scour in-non-bending vege- tation. The results showed that it is the initial introduction of vegetation into bare (root-free) bank conditions that produces the greatest increase in scour resistance and that subsequent increases in vegetation density bring about relatively lower increases in scour resistance. However, in all the vegetation densities studied, root- permeated so-ils contributed significantly to scour resistance in low flows especially through low vegetation densities. Compared to root- free soil conditions, sandy clay loam soils permeated with 1.8 g/CM3 of roots increased their scour resistance by more than 400%. Althgouh these results may only be indicative of the low flow depths as would exist in shallow grassed channels commonly used for agricultural run- off drainage, they nevertheless highlight the importance of root density in contributing to the total flow resistance of grassed channel banks. The bank stability analysis indicated that for low channel banks (1.5m high), grass roots can stabilise banks with even vertical slopes against toe and slope vailures. For high (2.25m) and vertical bank conditions, the results indi- cate that the effects of increases in root density may need to be com- plemented by bank shaping in order to achieve stability. The scour and bank stability findings indicate that the three most important charac- teristics for the selection of grass vegetation for bank protection are quick establishmentg the development of a stiff shoot system and a strong root mat.